Relationship of MR elastography determined liver stiffness with cardiac function after Fontan palliation. Issue 6 (8th November 2013) - Wallihan, Daniel B.; Podberesky, Daniel J.; Marino, Bradley S.; Sticka, Joshua S.; Serai, Suraj
<x xml:space="preserve">Abstract</x> Purpose To use MR elastography to assess liver stiffness in patients with congenital heart disease palliated with the Fontan procedure and correlate findings with cardiac index and other functional parameters obtained during cardiac MRI. Materials and Methods We performed a retrospective study of 14 patients (15 examinations) with Fontan circulation who underwent both cardiac MRI and liver MR elastography (MRE) on the same day. Liver stiffness was determined by calculating the mean liver stiffness from four slice locations. The cardiac index and other flow measurements were calculated from phase contrast MR imaging. Results The MRE was abnormal on all examinations with a median liver stiffness of 4.0 kPa (range, 3.4–6.2 kPa; normal adult liver stiffness is < 2.51 kPa). The cardiac index decreased as the duration of Fontan circulation (Fontan duration) increased (P = 0.005). We found a statistically significant inverse correlation between liver stiffness and cardiac index (P = 0.02), as well as the ejection fraction (P = 0.002). Patients with long Fontan durations (≥20 years) had greater liver stiffness compared with those having a shorter duration (P = 0.02). Conclusion MRE shows promise as a monitoring tool in the Fontan population, demonstrating an elevated liver stiffness in all patients, which inversely correlated with the MR determined cardiac index. J. Magn. Reson. Imaging 2014;40:1328–1335. © 2014 Wiley Periodicals, Inc.